Stock Price Forecasting Accuracy Analysis using Mean Absolut Deviation (MAD) and Mean Absolute Percentage Error (MAPE) on Smoothing Moving Average and Exponential Moving Average Indicator (Empirical Study 10 LQ 45 Stock with Largest Capitalization from pe - Halimawan, Alam Akbar; Sukarno, Subiakto (The Indonesian Journal of Business Administration, 2013)
Indonesia stock market crash of 2008, in general the majority due to external factors. The recovery of the world economy had a positive impact on economic growth in Indonesia. LQ 45 stock is a stock that has a market capitalization of 45 stocks are the most liquid and capitalized great. Based on data obtained from sources (www.idx.co.id), the condition of the development of the stock price index LQ 45 from the fourth quarter of 2009 until the third quarter of 2010 increased by 99.75%. The situation above can be analyzed through technical analysis. Moving Average indicator provides information signal sale or purchase, as the determinant of the ongoing trend., Knowing the trend reversal (reversal), and Moving Average can be used to gain support and resistance. In general, there are several indicators to measure the accuracy of forecasting, the Mean Absolute Deviation (MAD), Mean Square Error (MSE) and Mean Absolute Error Percentage Error (MAPE). The samples used were the stocks that fall into the category LQ 45 in the period February 2013 - July 2013. The Result of Measurement showed that method with the smallest MAD and MAPE is the best method chosen to determine how much the stock price forecasting in a single month, the Exponential Moving Average method recommended by the company and the investors.Â Keyword: Smoothing Moving Average, Exponential Moving Average, Mean Absolute Deviation (MAD), Mean Absolute Percentage Error (MAPE),Â LQ 45)